King Lear - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1999)
"King Lear" by William Shakespeare is a tragedy written in late 1605 or early 1606. Set in pre-Roman Britain, the play follows an aging king who divides his kingdom among his daughters based on their declarations of love, triggering devastating consequences. Known for its dark tone and exploration of blindness and madness, the work depicts family betrayal, political chaos, and human suffering. Regarded as one of Shakespeare's supreme achievements, it is regularly cited as one of the greatest works of literature ever written. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_Lear
There are improved editions of this title. See eBook #100 (the Complete Shakespeare) as well as #1532 (this specific play).
Release date is 1999-06-01
Keywords: Tragedies (Drama); Fathers and daughters -- Drama; Inheritance and succession -- Drama; Lear, King (Legendary character) -- Drama; Britons -- Drama; Kings and rulers -- Drama; Aging parents -- Drama